2009
DOI: 10.1007/978-3-642-04636-0_22
|View full text |Cite
|
Sign up to set email alerts
|

Remote Hands-On Experience: Distributed Collaboration with Augmented Reality

Abstract: Abstract. One claim of Technology-Enhanced Learning (TEL) is to support and exploit benefits from distance learning and remote collaboration. On the other hand, several approaches to learning emphasize the importance of handson experience. Unfortunately, these two goals don't go well together with traditional learning techniques. Even though TEL technologies can alleviate this problem, it is not sufficiently solved yet -remote collaboration usually comes at the cost of losing direct hands-on access. The ARiSE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Other researchers have also distinguished the effects of extrinsic and intrinsic motivation on the individual's acceptance of various information technologies (Agarwal & Karahanna, 2000;Heijden, 2004;Shang et al, 2005;Teo et al, 1999;Venkatesh, 1999Venkatesh, , 2000. Although there are many studies targeting learning in virtual environments (Krauss et al, 2009;Thorsteinsson et al, 2010) as well as several studies targeting motivational aspects in elearning (Keller, 2006;Lee et al, 2005) as far as we know, there is no acceptance model reported for AR-based educational systems.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have also distinguished the effects of extrinsic and intrinsic motivation on the individual's acceptance of various information technologies (Agarwal & Karahanna, 2000;Heijden, 2004;Shang et al, 2005;Teo et al, 1999;Venkatesh, 1999Venkatesh, , 2000. Although there are many studies targeting learning in virtual environments (Krauss et al, 2009;Thorsteinsson et al, 2010) as well as several studies targeting motivational aspects in elearning (Keller, 2006;Lee et al, 2005) as far as we know, there is no acceptance model reported for AR-based educational systems.…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire has 28 closed items and 2 open questions, asking users to describe the most 3 positive and most 3 negative aspects. The first 24 closed items are targeting various dimensions of the ARTP such as ergonomics and usability (items 1-14), perceived utility (items 15-17), perceived enjoyment (items 18-21) and intention to use (items [22][23][24]. The last four items were to assess how the students overall perceived the platform as being easy to use, useful for learning, enjoyable to learn with, and exciting.…”
Section: Experiment Samples and Data Analysismentioning
confidence: 99%
“…Touching and holding real objects is increasing the students' motivation to learn and could better support active and collaborative learning [18], [22]. As AR technologies become more wide-spread, there is an increasing interest in their ergonomic quality.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, there is a statistically significant difference at the level of Significance (0.05) between the mean scores of the female students of the research group in the pre& post-measurement of the scale of attitude towards green education and its dimensions in favor of the post-measurement. (Krauß, et al, 2009;Qiao, et al, (Barsom, et al, 2016;Dhar, et al,…”
Section: Introductionmentioning
confidence: 99%